Effect of volatile boron species on the electrocatalytic activity of cathodes of solid oxide fuel cells - Chen, Kongfa; Ai, Na; Zhao, L.; Jiang, San Ping (The Electrochemical Society, Inc, 2013)
The effect of volatile boron species on the electrocatalytic activity, microstructure and phase stability of conventional La0.6Sr0.4Co0.2Fe0.8O3 (LSCF) and nano-structured LSCF infiltrated Gd0.1Ce0.9O1.95 (LSCF-GDC) electrodes of solid oxide fuel cell (SOFC) is studied. The cathodes were heat-treated at 700–800°C for 7-30 days in air in the presence of borosilicate glass. Heat-treatment in the presence of glass has a significantly detrimental effect on the microstructure and electrochemical activity of the cathodes. For example, the electrode polarization resistance (RE) of a freshly prepared LSCF cathode is 0.07 Ω cm2 at 800°C, and increases significantly to 84 Ω cm2 after heat-treated at 800°C for 30 days in the presence of glass. Similar degradation behavior was also observed on infiltrated LSCF-GDC electrodes. Present study shows that boron is not chemically compatible with LSCF and the interaction results in the disintegration and decomposition of LSCF perovskite structure, forming LaBO3 and Fe2O3. A reaction mechanism between volatile boron species and LSCF electrodes is proposed.